(untitled) (Vietnam Journal of Community Medicine, 2024)
Background and aims: Traditional growing rods (TGR) are a gold standard treatment for earlyonset scoliosis (EOS), it corrects deformity while still allowing for spinal and thoracic growth. The aim of this study was to determine the correction, growth of spine, and complications of dual growing rods technique in the management of EOS. Methods: Retrospective study. The EOS patients were treated by dual growing rods at HTO from 2010 to 8/2023. Results: 16 patients (6 males, 10 females), age at first operation was 8, the mean follow up time was 44,44 months. Overall, 80 lengthening procedures were performed, the average number of lengthening procedures being 5 per patient. The average time between two lengthening procedures was 8 months. The causes of scoliosis in this study were 10 idiopathic, 1 congenital, 3 syndromes (Von Reclinghausen). There were 13 main thoracic curves, 1 lumbar, 2 double curves. The mean coronal Cobb angle was improved from 69 to 25 degrees. The ratio of correction is 63,9%. The coronal balance was improved from 23,2mm to 10,7mm and SVA from 19,3mm to 12,9mm at the last follow up. T1-S1 height was significantly different at pre-op and post-op. The mean T1-S1growth is 5,98 cm, mean increase 1,62cm/year. There were 8 complications, including 1 pleural effusion, 1 superficial infection, 8 hardware related. 8 patients were growing graduatedly: 1 final fusion, 7 follow up with good correction. Conclusion: TGR is a safe, effective, good correction and maintains growing of spine for EOS. It is suitable for vietnamese patients.